Manajemen Bencana Pemerintah Kabupaten Garut Studi Kasus: Letusan Gunung Papandayan Tahun 2008 - CICI WIDIAN SARI; FITRIYAH .; MUHAMMAD ADNAN (Journal of Politic and Government Studies, 2016)
Volcanic eruption hazard is a threat with potentially catastrophic risks are very high in Garut regency. Therefore, researchers want to know how disater management of garut regency goverment in Papandayan volcano in 2008 as well as how community involvement in this countermeasures of disaster.. This study is a qualitative research that is a descriptive study using data analysis.This research is the ex post facto. Informants in this research is Tb Aro Haq who is the section head of preventif BPBD Garut regency once volunteers in the event of Papandayan volcano in 2008.The results shows that disaster management implementation of papandayan volcanic eruption in 2008 implemented in three stage is pre-disaster, disaster emergency response and post disaster. Paradigm developed in this disaster countermesures is a preventive paradigm in which the change from an emergency response to risk management.It is changing the way people to participate in this disaster countermeasures of all stage.Therefore, researcher suggests that governemnt together with the public and private sector should coordinate to organize disaster management activities of Garut regency and encourage preventive paradigm in countermeasures of disaster embodied in the form of policies, regulations and procedures of disaster remains to tle lowest level of government. Keywords       :  Disater management, Garut regency government, Community involvement, Papandayan volcano eruption in 2008